Physics of the soil medium organization part 1: thermodynamic formulation of the pedostructure water retention and shrinkage curves - Braudeau, Erik; Assi, Amjad T.; Boukcim, Hassan; Mohtar, Rabi (Frontiers in Environmental Science, 2014)
The equations used in soil physics to characterize the hydro-physical properties of the soil medium cannot be other than empirical since they do not take into account the multi-scale functional organization of the soil medium that is described in Pedology. To allow researching the correct formulation of the physical equations describing the soil medium organization and properties, a new paradigm of hydrostructural pedology is being developed. This paradigm is to establish the conceptual link between the classical Pedology and the soil-water physics (hydrostructural characterization and modeling of the soil medium). The paradigm requires the exclusive use of the concept of Structural Representative Elementary Volume (SREV) instead of the classical Representative Elementary Volume (REV) in any physical modeling of the hydrostructural behavior of the soil medium and of the links with the biotic or abiotic processes evolving within it. This article presents the development of the physical equations of the shrinkage curve and the soil water retention curve from the thermodynamic point of view according to the new paradigm. The new equations were tested and the theory validated using data of simultaneous measurement of both curves on a cylindrical soil sample (pedostructure). Implications of these results on the physical modeling in agro-environmental sciences are discussed.